MATH SOLVE

2 months ago

Q:
# Use the following graph of the function f(x) = 3x4 β x3 + 3x2 + x β 3 to answer this question: graph of 3 x to the fourth, minus x cubed, plus 3 x squared, plus x minus 3 What is the average rate of change from x = 0 to x = 1

Accepted Solution

A:

f(x) = 3x^4 - xΒ³ + 3xΒ² + x - 3

x = 0f(0) = 3(0)^4 - 0Β³ + 3(0Β²) + 0 - 3f(0) = 0 - 0 + 0 + 0 - 3f(0) = -3

f(1) = 3(1)^4 - 1Β³ + 3(1Β²) + 1 - 3f(1) = 3 - 1 + 3 + 1 -3f(1) = 7 - 4f(1) = 3

x = 0 : f(0) = -3x = 1 ; f(1) = 3

1 - 0 / 3 - (-3) = 1 / 6

x = 0f(0) = 3(0)^4 - 0Β³ + 3(0Β²) + 0 - 3f(0) = 0 - 0 + 0 + 0 - 3f(0) = -3

f(1) = 3(1)^4 - 1Β³ + 3(1Β²) + 1 - 3f(1) = 3 - 1 + 3 + 1 -3f(1) = 7 - 4f(1) = 3

x = 0 : f(0) = -3x = 1 ; f(1) = 3

1 - 0 / 3 - (-3) = 1 / 6